5 x - 7 = 3 x + 11
OR
- ( 5 x - 7 ) = 3 x + 11
Possibility 1:
5 x - 7 = 3 x + 11
Try to solve this equation.
The solution is x = 9
Possibility 2:
- ( 5 x - 7 ) = 3 x + 11
Try to solve this equation as well.
The solution is x = - 1 / 2
So the solutions are:
x = - 1 / 2 and x = 9
Check answers.
| 5 x - 7 | = | 3 x + 11 |
for x = - 1 / 2
| 5 ∙ ( - 1 / 2 ) - 7 | = | 3 ∙ ( - 1 / 2 ) + 11 |
| - 5 / 2 - 7 | = | - 3 / 2 + 11 |
| - 5 / 2 - 14 / 2 | = | - 3 / 2 + 22 / 2 |
| - 19 / 2 | = | 19 / 2 |
19 / 2 = 19 / 2
| 5 x - 7 | = | 3 x + 11 |
for x = 9
| 5 ∙ 9 - 7 | = | 3 ∙ 9 + 11 |
| 45 - 7 | = | 27 + 11 |
| 38 | = | 38 |
38 = 38
|5x-7|=|3x+11|
1 answer